The Face-to-Face Still-Face (FFSF) Paradigm in Clinical Settings: Socio-Emotional Regulation Assessment and Parental Support With Infants With Neurodevelopmental Disabilities - Giusti, Lorenzo; Provenzi, Livio; Montirosso, Rosario (Frontiers in Psychology, 2018)
Background. The Face-to-Face Still-Face (FFSF) paradigm is a well-acknowledged procedure to assess socio-emotional regulation in healthy and at-risk infants. Although it was developed mainly for research purposes, the FFSF paradigm has potential clinical implications for the assessment of socio-emotional regulation of infants with neurodevelopmental disabilities (ND) and to supporting parenting. Aim. The present paper describes the application of the FFSF paradigm as an evaluation and intervention tool in clinical practice with infants with ND and their parents. Methods. Theoretical and methodological insights for the use of the FFSF paradigm in the clinical setting are provided. Single-case vignettes from clinical practice further illustrate and provide exemplifications for the use of the FFSF with infants with ND and their parents. Results. From a clinical point of view, the use of the FFSF paradigm (1) offers a unique observational perspective on socio-emotional regulation in infants with ND and (2) enhances parents’ sensitivity to their infants’ behavior. Discussion. The FFSF paradigm appears to be a useful tool for clinical assessment of socio-emotional regulation in infants with ND and promote the quality of parenting and early parent-infant interaction.